2011
DOI: 10.4103/0972-5229.78219
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes assessed by point-of-care testing - Are the values comparable with results obtained from the central laboratory?

Abstract: Background and Aims:When dealing with very sick patients, the speed and accuracy of tests to detect metabolic derangements is very important. We evaluated if there was agreement between whole blood electrolytes measured by a point-of-care device and serum electrolytes measured using indirect ion-selective electrodes.Materials and Methods:In this prospective study, electrolytes were analyzed in 44 paired samples drawn from critically ill patients. Whole blood electrolytes were analyzed using a point-of-care blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 12 publications
2
47
1
Order By: Relevance
“…An understanding of differences, if any, in results of the same test performed on these machines and their clinical relevance, would be crucial to ascertain the implications in clinical decision‐making. The existing literature comparing these tests yielded mixed results and use of small sample sizes, study population, and method of sampling may have contributed to the discrepancy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An understanding of differences, if any, in results of the same test performed on these machines and their clinical relevance, would be crucial to ascertain the implications in clinical decision‐making. The existing literature comparing these tests yielded mixed results and use of small sample sizes, study population, and method of sampling may have contributed to the discrepancy …”
Section: Introductionmentioning
confidence: 99%
“…The existing literature comparing these tests yielded mixed results and use of small sample sizes, study population, and method of sampling may have contributed to the discrepancy. [5][6][7][8][9] We tested the hypothesis that results of the same test performed on BGA machine and AA machine have high degree of concordance in an unselected population of critical care patients and that the two test methods could be used interchangeably. To test this hypothesis, we retrospectively analyzed the concordance between the electrolyte and hemoglobin values obtained from these two test methods using the largest sample size reported to date.…”
mentioning
confidence: 99%
“…[2] We agree with the statement, “two samples that are processed in different times can have different laboratory data”. In our paper, we have stated that paired samples were collected at the same time from each patient.…”
mentioning
confidence: 69%
“…[40] found that while agreement between whole blood and serum was good, differences were large and clinically significant at concentrations below 3 mmol/L (whole blood measurements were up to 1 mmol/L lower compared to serum). The authors had used plastic lithium coated ABG syringes (DRIHEP A-LINE arterial blood gas collection syringe, 3.0 mL volume, 1.6 mL recommended draw Becton Dickinson Diagnostics ® , Plymouth, UK) for blood gas analysis to minimize the effect of heparin flushes and also determined that their pneumatic system did not significantly alter the electrolyte values.…”
Section: Whole Blood Testingmentioning
confidence: 99%